1988
DOI: 10.1177/000331978803901106
|View full text |Cite
|
Sign up to set email alerts
|

Value and Limits of "Critical Auscultation" of Neck Bruits

Abstract: Within a group of 2,000 patients evaluated, most of them with symptoms of cerebrovascular insufficiency, 441 had a monolateral or bilateral cervical bruit. The 627 sides with an audible bruit were divided into main groups (A) symptomatic (TIA and/or stroke homolateral to the bruit), (B) possibly symptomatic (non-side-related symptoms), (C) asymptomatic (C1, in totally asymptomatic patients; C2, in patients with symptoms dependent on the hemisphere contralateral to the cervical bruit). Each patient was studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
1
1
Order By: Relevance
“…However, other investigators documented a fairly low specificity (40 -44%) for a mixed patient population with or without cerebrovascular symptoms [19,22,25,28]. In our sample of asymptomatic patients undergoing CABG the specificity of cervical bruit was 98.6% for all grades of internal carotid artery disease and 93.5% for occlusive disease with haemodynamic impairment.…”
Section: Discussioncontrasting
confidence: 51%
“…However, other investigators documented a fairly low specificity (40 -44%) for a mixed patient population with or without cerebrovascular symptoms [19,22,25,28]. In our sample of asymptomatic patients undergoing CABG the specificity of cervical bruit was 98.6% for all grades of internal carotid artery disease and 93.5% for occlusive disease with haemodynamic impairment.…”
Section: Discussioncontrasting
confidence: 51%
“…In the study of Ghilardi, carotid kinking and occlusion were regarded as a carotid lesion[ 9 ]. Floriani et al found a sensitivity and specificity of carotid bruits to predict a carotid lesion of 84% and 40%, respectively[ 10 ], rendering a positive likelihood percentage (PLP) value of 29% and a negative likelihood percentage (NLP) value of 60%. Sauve et al found a sensitivity, specificity, positive and negative likelihood percentages of 63%, 61%, 38% and 39%, respectively, for 70–99% stenoses when studying the NASCET-population[ 11 ].…”
Section: Discussionmentioning
confidence: 99%